Comparative effects of epigallocatechin-3-gallate supplementation in skim milk, egg yolk-citrate, and combined extenders on the spermatozoa quality of Ettawah crossbred bucks during storage at 5 °C - Muhammad Ikmal Robih; Anas Bad’rosana Prawindi; Tatik Hernawati; Budi Utomo; Suherni Susilowati; Tri wahyu Suprayogi; Sri Pantja Madyawati; Kadek Rachmawati; Mustofa Helmi Effendi; Yeni Dhamayanti (Universitas Airlangga, 2025)
This study aimed to determine the quality of Ettawah crossbred buck semen diluted in skim milk, egg yolk-citrate extenders, or their combination, supplemented with epigallocatechin-3-gallate (EGCG). Semen was collected from Ettawah crossbred bucks using an artificial vagina. Six ejaculates were used for replication and divided into three extender treatments: T1, skim milk; T2, egg yolk-citrate; and T3, a combination of both, each supplemented with 1.5 µg/mL EGCG. The extended semen was stored in a refrigerator at 5 °C. Diluted samples were evaluated every 24 hours until spermatozoa motility declined to 30%, the minimum requirement for artificial insemination. The results showed that spermatozoa motility, viability, plasma membrane integrity, and morphological abnormality decreased during six days of storage at 5 °C. Spermatozoa motility remained above 30% for five days in T1 (36.50±1.22%) and T2 (41.67±2.06%), and for six days in T3 (43.33±1.03%). On day six, semen in the combined extender supplemented with EGCG (T3) showed significantly higher motility, viability, and membrane integrity, and lower morphological abnormalities (p <0.05) than the other treatments. In T2, all spermatozoa quality parameters were higher (p <0.05) than in T1. It can be concluded that the combined skim milk-egg yolk-citrate extender containing 1.5 µg/mL EGCG best maintained the spermatozoa quality of Ettawah crossbred bucks during six days of storage at 5 °C. Based on spermatozoa motility, the semen remained suitable for artificial insemination.